ANALISIS NERACA AIR KAWASAN HUTAN TANAMAN KAYUPUTIH DI KABUPATEN GUNUNG KIDUL DAERAH ISTIMEWA YOGYAKARTA - , Rahardyan Nugroho, Drs ([Yogyakarta] : Universitas Gadjah Mada, 2012)
flow in a catchment area for a certain period of the circulating water. In the hydrological system of watershed, evapotranspiration is one form of water loss. Incertain conditions, evapotranspiration will affect water availability for plants (soil moisture) or even further will also affect the total water supply (groundwater). The purpose of this study was: 1) Knowing the condition of water availability (soil moisture) under kayuputih plants on kayuputih forest plants, 2) Knowing the condition of the water balance on kayuputih forest plants